Orient/East-Med Corridor: Challenges and demands for the rail network policies - Bardo Hörl (Spatial and transport infrastructure development in Europe: Example of the Orient/East-Med Corridor, 2019)
As rail represents an efficient and sustainable transport system, the Trans-European railway network has become subject to special attention from European transport policy. The political objectives are to shift 30 % of freight to rail by 2030, 50 % by 2050, and to reduce passenger trips on road and in the air. These make it necessary to develop the defined TEN-T core network rail corridors as a priority, which means eliminating bottlenecks along the corridors and increasing capacities and operation quality. This concerns the Orient/East-Med (OEM) Core Network Corridor as well. Considerable parts of the infrastructure of the railway network along the OEM Corridor is not compliant with some of the technical thresholds set out by EU-Regulation 1315/2013. In the meanwhile the EU and the affected states have established activities for extending the core network corridors to the Western Balkans states. In 2015, the European Commission adopted a Joint Statement of the Prime Ministers of six Western Balkans states (WB6), which contains a list of specified Core Network links and Priority Projects for the extension of the TEN-T network to the Western Balkans. During additional common summits of the EU and the WB6, an indicative extension network has been more and more concretized. To date the process has led to the establishment of a common EU-Western Balkans Transport Community signed in 2017, which aims to help WB6 countries integrate into the EU by creating closer transport ties or connections. A continuing aspect is the importance of the OEM Corridor for the Chinese Belt and Road Initiative as a hinterland connection between the sea port of Piraeus (GR) and the central and eastern European countries. – – Als effizienter und nachhaltiger Verkehrsträger hat die Schiene auch in der europäischen Verkehrspolitik und somit auch im transeuropäischen Eisenbahnnetz besondere Aufmerksamkeit bekommen. So sind als verkehrspolitische Ziele die Verlagerung von 30 % des Güterverkehrs auf die Schiene bis 2030, von 50 % bis 2050 und die Reduzierung des Personentransportes auf der Straße und in der Luft formuliert. Diese Ziele erfordern die vorrangige Entwicklung definierter TEN-V-Kernnetz-Eisenbahnkorridore. Dies umfasst die Beseitigung von Engpässen entlang der Korridore, sowie die Steigerung von Kapazitäten und Betriebsqualitäten. Dies betrifft auch den Orient/ East-Med (OEM) Core Network Corridor. Große Teile der Infrastruktur des Eisenbahnnetzes entlang des OEM Corridors entsprechen nicht den technischen Standards der EU-Verordnung 1315/2013. Mittlerweile haben die EU und die betroffenen Staaten Maßnahmen zur Ausweitung der Kernnetzkorridore auf die Westbalkanstaaten eingeleitet. Im Jahr 2015 verabschiedete die Europäische Kommission eine Gemeinsame Erklärung der Premierminister von sechs Westbalkanstaaten (WB6), die eine Liste spezifischer Kernnetzwerkverbindungen und prioritärer Projekte für die Ausdehnung des TEN-V-Netzes auf den Westbalkan beinhaltet. Bei weiteren gemeinsamen Gipfeltreffen der EU und der WB6 wurde ein indikatives Erweiterungsnetz zunehmend konkreter. Dieser Prozess hat bisher zur Gründung einer gemeinsamen Verkehrsgemeinschaft EU-Westbalkan geführt, die 2017 unterzeichnet wurde und darauf abzielt, die Integration der WB6-Länder in die EU durch engere Verkehrsbeziehungen oder -verbindungen zu unterstützen. Ein weiterer Aspekt ist die Bedeutung des OEM Corridors für die Chinese Belt and Road Initiative als Hinterlandverbindung zwischen dem Seehafen Piräus (GR) und den mittel- und osteuropäischen Ländern.
urn:nbn:de:0156-0952070; hdl:10419/213084; https://econpapers.repec.org/RePEc:zbw:arlfob:12
Keywords: 710; TEN-T; railway network; rail infrastructure; rail freight transport; Western Balkans States; New Silk Road; TEN-V; Eisenbahnnetz; Schieneninfrastruktur; Schienengüterverkehr; Westliche Balkanstaaten; Neue Seidenstraße